Wildfire Air Pollution and Rates of Cardiovascular Events and Mortality in Northern California in 2018 - Stacey E. Alexeeff; Stephen K. Van Den Eeden; Kamala Deosaransingh; Stephen Sidney; Noelle S. Liao; Jamal S. Rana (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We examined the association between acute cardiovascular disease (CVD) events and wildfire air pollution in California in 2018. Methods The study included adult (≥18 years) members of Kaiser Permanente Northern California, an integrated health care system. Outcomes included CVD events (hospitalizations for acute myocardial infarction, heart failure, or stroke, and CVD death) and death from any cause. Fine particulate air pollution (particulate matter <2.5 microns in diameter; PM2.5) exposure was assessed in categories (Good <12 μg/m3, Moderate 12–34 μg/m3, High ≥35 μg/m3) and continuously. Poisson time series regression was used to model daily event rates during July 1 to December 31, 2018, using a spline to adjust for long‐term time trends. We calculated rate ratios (RR) to estimate the association between wildfire air pollution and daily rate of CVD events and deaths. Results Our study included 3.2 million adults with a total follow‐up of 587.9 million person‐days. High PM2.5 concentrations during the Mendocino Complex wildfire in July to August was associated with an increased rate of CVD events (RR, 1.231 [95% CI, 1.039–1.458]) and death (RR, 1.358 [95% CI, 1.128–1.635]) compared with Good PM2.5 concentrations. In contrast, there was no evidence of increased risk during the Camp wildfire in November (RR for CVD events, 0.966 [95% CI, 0.894–1.044]; RR for all‐cause mortality, 0.985 [95% CI, 0.904–1.074] High versus Good PM2.5 concentrations). Conclusions There was some evidence of increased rates of CVD events and death during wildfires, but results were inconsistent. With ongoing climate change, large wildfires are a pressing public health concern and future work is needed to understand differences in health outcomes by wildfire.